Corruption in India : agenda for action - Guhan, Sanjivi; Samuel, Paul, 1930- (New Delhi : Vision Books, 1997)
Contributed articles.
Includes bibliographical references (p. [305]-308) and index.
Keywords: Political corruption -- India